Potentiation of GATA-2 Activity through Interactions with the Promyelocytic Leukemia Protein (PML) and the t(15;17)-Generated PML-Retinoic Acid Receptor α Oncoprotein - Tsuzuki, Shinobu (American Society for Microbiology, 2000)
The hematopoietically expressed GATA family of transcription factors function as key regulators of blood cell fate. Among these, GATA-2 is implicated in the survival and growth of multipotential progenitors. Here we report that the promyelocytic leukemia protein (PML) can complex with GATA-2 and potentiate its transactivation capacity. The binding is mediated through interaction of the zinc finger region of GATA-2 and the B-box domain of PML. The B-box region of PML is retained in the PML-RARα (retinoic acid receptor alpha) fusion protein generated by the t(15;17) translocation characteristic of acute promyelocytic leukemia (APL). Consistent with this, we provide evidence that GATA-2 can physically associate with PML-RARα. Functional experiments further demonstrated that this interaction has the capacity to render GATA-dependent transcription inducible by retinoic acid, raising the possibility that GATA target genes may be involved in the molecular pathogenesis of APL.